2016
DOI: 10.1002/path.4682
|View full text |Cite
|
Sign up to set email alerts
|

Decreased FOXJ1 expression and its ciliogenesis programme in aggressive ependymoma and choroid plexus tumours

Abstract: Well-differentiated human cancers share transcriptional programs with the normal tissue counterparts from which they arise. These programs broadly influence cell behavior and function and are integral modulators of malignancy. Here, we show that the master regulator of motile ciliogenesis, FOXJ1, is highly expressed in cells along the ventricular surface of the human brain. Strong expression is present in cells of the ependyma and the choroid plexus as well as in a subset of cells residing in the subventricula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 73 publications
(169 reference statements)
4
25
1
Order By: Relevance
“…We recently reported that FOXJ1 is expressed in the nucleus of ciliated ependymal cells that line the ventricle of the human brain, as well as in well-differentiated ependymoma and choroid plexus tumors (39, 41). Using an immunohistochemistry protocol developed for that study, we analyzed the expression of FOXJ1 protein in a panel of sixteen Rathke’s cleft cysts (Supplemental Table 1; Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently reported that FOXJ1 is expressed in the nucleus of ciliated ependymal cells that line the ventricle of the human brain, as well as in well-differentiated ependymoma and choroid plexus tumors (39, 41). Using an immunohistochemistry protocol developed for that study, we analyzed the expression of FOXJ1 protein in a panel of sixteen Rathke’s cleft cysts (Supplemental Table 1; Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Such markers may not only improve diagnostic accuracy, but may also provide useful insights into the biology of lesions, which may suggest novel therapeutic interventions. Characterization of the motile ciliogenesis program in ependymoma via FOXJ1 immunohistochemistry has already yielded interesting insights into disease biology (39). We expect that FOXJ1 and TUBA4A/ARL13B immunohistochemistry will prove useful in the evaluation of other tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10). Comparing to other brain tumour types, FOXJ1 expression was increased in ependymomas, with the highest levels in PF-EPN-B tumours 16 (Extended Data Fig. 10).…”
mentioning
confidence: 89%
“…A recent study published by Abedalthagafi and colleagues in the Journal of Pathology also demonstrated that assessing expression of FOXJ1 and RFX factors could serve the diagnosis and prognosis of ependymal and choroid plexus tumours [13]. The ventricles of the brain are lined by multiciliated cells and FOXJ1 as well as RFX2 expression is normally high in the ependyma and choroid plexus.…”
Section: P Walentekmentioning
confidence: 99%